The Need to Teach Thinking from an Islamic Perspective - Abu Elkheir, Gasim Omer (Tafakkur; مجلد 3 عدد 2 (2001), 2001)
In recent years there has been a widespread recognition of importance of thinking in the learning/teaching processes especially among western educators (Raths .et al: 1967 and Ruggiero, 1988). Accordingly, the fundamental characteristics of an educated person have been viewed as requirements for responsible citizenship in society as well as employment skills of a wide range of jobs. Creating such a person depends on different factors that might affect learning/teaching process in general, and curriculum in particular. For that, striving for excellence in education, a curriculum’s effectiveness was seen in the context of its ability to achieve definite objectives stated by curricula’s designers or educational authorities.